KINERJA KEUANGAN LEMBAGA KEUANGAN KELURAHAN PATIHAN KECAMATAN MANGUHARJO KOTA MADIUN PADA MASA PANDEMI COVID-19 - Desanto Wiwoho, Rino (Widya Warta, 2021)
The COVID-19 pandemic in Indonesia since 2019 has been a difficult time for most people. The impact of the pandemic is affecting all sectors. The pandemic also affects the economy. The economic slowdown was felt in almost all economic sectors, especially starting from the second quarter of 2019. Therefore, it was deemed necessary to look at the financial performance of LKK Patihan both during the pandemic and during the pre-pandemic period. Data was obtained from Patihan LKK in the form of financial statements of December 31, 2018, 2019, and 2020. The data were analyzed using the Liquidity Ratio, Activity Ratio, Profitability Ratio, and Solvency Ratio. Based on the four ratio analysis, it was known that during the pandemic, Patihan LKK's financial performance did not experience a significant decline. During the pandemic, LKK Patihan's liquidity ratio increased. The activity ratio was known to increase in 2019 and decrease in 2020. From the profitability ratio, it was known that the percentage of profit generated from total assets was decreasing. The percentage of profit generated from total capital was decreasing, while the solvency ratio was increasing. It is expected that the profitability ratio can be increased by converting uncollectible receivables into cash. With sufficient cash, it is possible for LKK Patihan to turn cash and generate profits.